The Rising Tide : A New Look at Water and Gender - Das, Maitreyi Bordia (World Bank, Washington, DC, 2017)
The report reviews a vast body of literature to present a "thinking device" that visualizes water as an asset, a service, and a "space." It shows water as an arena where gender relations play out in ways that often mirror inequalities between the sexes. And it examines norms and practices related to water that often exacerbate ingrained gender and other hierarchies. Informal institutions, taboos, rituals, and norms all play a part in maintaining these hierarchies and can even reinforce gender inequality. The report's key message is clear—interventions in water-related domains are important in and of themselves and for enhancing gender equality more broadly. The report discusses examples of initiatives that have had intended and unintended consequences for gender equality, and makes the important point that gender inequality does not always show up where we might expect.